CONSERVATION TILLAGE PRACTICES FOR ENHANCED PRODUCTIVITY IN SUGARCANE–PADDY SYSTEM - K V , RAMANA MURTHY; P V K , JAGANNADHA RAO (The Journal of Research ANGRAU, 2026)
A field study was carried out at Regional Agricultural Research Station farm, Anakapalle from 2022-23 to 2024-25 for three years to study the feasibility of conservation tillage practices and its impact on crop establishment, growth of crop and weed, and productivity of Sugarcane in Sugarcane-Paddy cropping system. The trial was carried out using a strip plot design with three replications. The main plot factor comprised of conservation tillage practices and weed management techniques in sub plots. The cropping cycle of sugarcane planting in furrows with ridgemar in rice fallows + Cowpea during first year followed by Sugarcane (ratoon)+Cowpea during second year andtaking up Pulse-Green manure-Paddy with minimal tillage and sowing during the third year in addition to chemical weed control methods for effective weed management was found suitable to improve the overall productivity of Sugarcane-paddy system(217.47 t ha-1) and economically profitable instead of the normal conventional system.